Indemnities for the Benefit of Others - FURMSTON, Michael Philip (Institutional Knowledge at Singapore Management University, 2011)
The requirement of consideration, the doctrine of privity of contract and the general rule that a plaintiff can only recover in respect of its own loss, present obstacles to contractual promises to indemnify third party beneficiaries. This article considers the obstacles, and the various devices used to clear them, from both a commercial and a legal perspective.